355 Fundic Gland Polyp Biopsies: A Cost-Effectiveness Analysis at One Academic Center. (11th January 2018) - Kertowidjojo, Elizabeth; Zee, Sui
Abstract: Fundic gland polyps (FGPs) are the most common gastric polyp in the US, found in up to 5.9% of all adults undergoing esophagogastroduodenoscopy (EGD). They are usually incidental findings and considered to be a benign entity with virtually no malignant potential. When found during EGD, the current practice is to obtain a biopsy. In 2010, almost 3 million EGDs were performed in the US, leading to over 28, 000 FGP biopsies and an estimated cost of almost 7 million. This number will grow, as the number of EGDs rises. The diagnosis of FGP does not require further intervention or surveillance. Dysplasia in sporadic FGP is rare, and its clinical implication is uncertain. We hypothesize that the practice of routine FGP biopsy is unnecessary, and its elimination will reduce cost without compromising patient care. We performed a search of our pathology database for cases of FGPs diagnosed from endoscopic biopsies at Stony Brook University Hospital (SBUH) from 2010 to 2015. Data was also collected regarding the presence of dysplasia, and the patient's gender, age, and race. We found that from 2010 to 2015, the number of FGP cases diagnosed at SBUH has increased by 48%. The estimated annual cost rose by almost 15, 000. Only four cases of dysplasia were identified, constituting 0.5% of all diagnosed FGPs. We conclude that the increasing rate of FGP diagnosis predicts a continuing trend of rising costs. Given the benign nature of this entity, the cost does not translate to an altered treatment course or improved patient outcome. Predicting typical FGPs based on endoscopic features has been shown to be reliable, making a histological diagnosis unnecessary. Ultimately, the practice of routine FGP biopsy is one based more on defensive medicine rather than clinical impact and can be eliminated to reduce costs without compromising patient care.